Epidemiological profile of hospitalizations for mental and behavioral disorders due to alcohol use in the metropolitan region of Belém Pará (Research, Society and Development, 2024)
Due to a significant incidence of hospitalizations due to alcohol use, the effects of this consumption are considered health risk factors and chronic and acute damage, causing a public health problem that requires treatment to reduce health impacts. Objective: To analyze the profile of patients hospitalized with a diagnosis of mental and behavioral disorders due to alcohol use in the Metropolitan Region of Belém in the state of Pará, from 2019 to 2023. Methods: This involves applying the descriptive method, with documentary technique, exploratory in nature and with a quantitative approach. The data will be collected directly from DATASUS/TABNET (Informatics Department of the Unified Health System) with relevant information from the Metropolitan Region of Belém. The result of this research from the sample analyzed to characterize the profile of patients hospitalized with mental and behavioral disorders using alcohol in the Metropolitan Region of Belém -RIDE (CID 10), in the period 2019 -2023, there were 41 hospitalizations. 38 (93%) were male and 3 (7%) were female, with the highest incidence of hospitalizations being individuals in the age group (40 to 49 years) which corresponds to 16 (41%) of hospitalizations. Final Considerations: it is considered that this study has evidenced the possible effective strategies and interventions presented in the literature to understand the impacts of alcohol use and mental health problems of individuals with Mental and Behavioral Disorders in the Metropolitan Region of Belém - RIDE.